Endophytic growth of Clonostachys rosea in tomato and Arabidopsis - Alvarez Nordström, Sofia (2014)
In the future, an increased food demand together with restrictions of pesticide use will require new options of disease management within agriculture. Usage of biological control agents (BCAs) is a feasible alternative. For example, BCAs may reduce pathogen attacks in plants by induced resistance. In this strategy the BCA initially elicits defence responses in the plant. Signalling hormones such as salicylic acid (SA) and jasmonic acid (JA) are synthesised and down-stream defence genes expressed. This interaction leads to faster and stronger defence response of the plant against later pathogen attack. Clonostachys rosea strain IK726 is a BCA under development. It has been reported to endophytically colonize the roots of cucumber and to elicit the expression of defence- related genes in wheat and canola. Induced resistance by C. rosea against grey mould, Botrytis cinerea, was studied for greenhouse tomato and the model plant Arabidopsis thaliana. C. rosea was found to colo- nize the roots of tomato and A. thaliana, both on the surface and endophytically. This in- teraction with the plant also triggered defence responses, in tomato SA-related defence gene CHI9 was induced, while in A. thaliana expression of JA-related defence gene PDF 1.2 and camalexin biosynthesis gene PAD3 were induced. Yet, these responses were only weakly expressed, and when tomato and A. thaliana were later challenged with B. cinerea there was no visible suppression of the infection. In summary, C. rosea was able to colo- nize both tomato and A. thaliana endophytically and to induce defence-related gene ex- pression changes, but did not promote plant growth or induce systemic resistance against infection of B. cinerea in the leaves.